Beyond the "gentry aesthetic": elites, Received Pronunciation and the dialectological gaze. Issue 3 (27th May 2017) - Britain, David
ABSTRACT: I argue here that sociolinguistic studies of elite accents have largely been trapped in a methodological and theoretical cul-de-sac, isolated from other work in dialectology, blinkered by outdated concepts of elite status, and entangled with ideologies about standard accents. I begin by presenting the hurdles that face scholars of elite accents in English. There have, firstly, been few robust empirical investigations of English elite accents and our understanding of them has not been integrated into theorisations of language variation and change. Secondly, there has been a consistent but problematic "gentry aesthetic" in work on such accents – a concentration on the aristocratic, landed, private school-educated elite. Thirdly, a cycle of ideological linkages between phonetic descriptions of English, elites and accent standards has led to an overpowering dominance of "Received Pronunciation" (RP) in debate about upper-class accents, preventing us from examining the everyday accents of elites independent both of century-old descriptions of RP and of the assumption that elite accents are standard accents. I conclude by outlining what a dialectology of elites might look like, freed from overpowering orientations to RP and the standard, and enabling elite accents to be integrated into sociolinguistic models of language variation.